Appropriate Rule for Self-Regulation in Thai Stock Exchange Market - Winyuhuttakit, Pakorn; Kesaprakorn, Nares (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2022)
Self-regulation is a form of regulation which allows members of professional group or business group to gain the role of regulating themselves and the stock exchange of Thailand also adopts self-regulation form. However, during the study period (before December 31, 2021), the Securities and Exchange Act B.E. 2535 does not certify Self-Regulatory Organization (SRO) status. This creates uncertainty as to which organizations have SRO status and what duty and liability they should have. Moreover, the rules for self-regulatory under the Securities and Exchange Act B.E. 2535 are not sufficient to protect stakeholders in the stock exchange since they create unfairness to other stakeholders and cause conflict of interest between SRO members and the investors. Therefore, appropriate legal framework to certify SRO status should be established for both levels of stock exchange and securities association, and the rules of self-regulation should be improved to adequately support fairness, transparency and investor protection. This research uses document study by comparing the rule between Thailand and the selected country as case study i.e. Malaysia, South Korea and the United States.